Thermophysical Properties of Binary Mixtures of Dimethylsulfoxide with 1-Phenylethanone and 1, 4-Dimethylbenzene at Various Temperatures. (24th February 2014) - Gill, Harmandeep Singh; Rattan, V. K.
Abstract : This research article reports the experimental results of the density, viscosity, refractive index, and speed of sound analysis of binary mixtures of dimethylsulfoxide (DMSO) + 1-phenylethanone (acetophenone) and + 1, 4-dimethylbenzene ( para -xylene) over the whole composition range at 313.15, 318.15, 323.15, and 328.15 K and at atmospheric pressure. The excess molar volumes (V E ), viscosity deviations (Δ η ), excess Gibbs energy of activation (G E ), deviations in isentropic compressibility (K S E ), deviations in speed of sound (u E ), and deviations in the molar refraction (Δ R ) were calculated from the experimental data. The computed quantities were fitted to the Redlich-Kister equation to derive the coefficients and estimate the standard error values. The viscosities have also been correlated with two, and three-parameter models, that is, Heric correlation, McAllister model, and Grunberg-Nissan correlation, respectively.